Development of 111In-labeled exendin(9-39) derivatives for single-photon emission computed tomography imaging of insulinoma. Issue 4 (15th February 2017) - Kimura, Hiroyuki; Matsuda, Hirokazu; Ogawa, Yu; Fujimoto, Hiroyuki; Toyoda, Kentaro; Fujita, Naotaka; Arimitsu, Kenji; Hamamatsu, Keita; Yagi, Yusuke; Ono, Masahiro; Inagaki, Nobuya; Saji, Hideo
Graphical abstract: Abstract: Insulinoma is a tumor derived from pancreatic β-cells, and the resulting hyperinsulinemia leads to characteristic hypoglycemia. Recent studies have reported the frequent overexpression of glucagon-like peptide-1 receptor (GLP-1R) in human insulinomas, suggesting that the binding of a radiolabeled compound to GLP-1R is useful for the imaging of such tumors. Exendin(9-39), a fragment peptide of exendin-3 and -4, binds GLP-1R with high affinity and acts as an antagonist. Accordingly, radiolabeled exendin(9-39) derivatives have also been investigated as insulinoma imaging probes that might be less likely to induce hypoglycemia. In this study, we synthesized a novel indium-111 ( 111 In)-benzyl-diethylenetriaminepentaacetic acid ( 111 In-BnDTPA)-conjugated exendin(9-39), 111 In-BnDTPA-exendin(9-39), and evaluated its utility as a probe for the SPECT imaging of insulinoma. natIn-BnDTPA-exendin(9-39) exhibited a high affinity for GLP-1R (IC50  = 2.5 nM), stability in plasma, and a specific activity that improved following reactions with a solvent and solubilizer. Regarding the in vivo biodistribution of 111 In-BnDTPA-exendin(9-39) in INS-1 tumor-bearing mice, high uptake levels were observed in tumors (14.6% ID/g at 15 min), with corresponding high tumor-to-blood (T/B), tumor-to-muscle (T/M), and tumor-to-pancreas (T/P) ratios (T/B = 2.55, T/M = 22.7, T/P = 2.7 at 1 h). The pre-administration of excess nonradioactive exendin(9-39) significantly reduced accumulation in both the tumor and pancreas (76% and 68% inhibition, respectively) at 1 h after 111 In-BnDTPA-exendin(9-39) injection, indicating that the GLP-1R mediated a majority of 111 In-BnDTPA-exendin(9-39) uptake in the tumor and pancreas. Finally, 111 In-BnDTPA-exendin(9-39) SPECT/CT studies in mice yielded clear images of tumors at 30 min post-injection. These results suggest that 111 In-BnDTPA-exendin(9-39) could be a useful SPECT molecular imaging probe for the detection and exact localization of insulinomas.